2019
DOI: 10.1002/ente.201900389
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and Nonreactive Ball Milling of Tin‐Antimony (Sn‐Sb) Composites and Their Use as Electrodes for Sodium‐Ion Batteries with Glyme Electrolyte

Abstract: Tin (Sn), antimony (Sb), as well as their intermetallic compound SnSb are potential high‐capacity negative electrodes for lithium‐ or sodium‐ion batteries. Starting from bulk Sn and Sb, the effect of ball milling in sodium‐ion half cells with a diglyme‐based electrolyte is studied. Nonreactive ball milling of Sn, Sb, and carbon leads to intimately mixed but largely phase‐separated composites (Sn + Sb) with electrochemical sodiation behavior being the sum of the individual phases. Thereby, Sb shows an unusual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…[17,20] Interestingly, the negative impact of diglyme on conversion anodes comprising antimony oxide, as reported herein, was not observed with conversion anodes comprising tin compounds. [18,21] Hence, the unique interactions between Sn cations and diglyme molecules do not exist when we change the central transition metal involved in the electrode's conversion reactions. This situation emphasizes the importance of a proper adjustment of specific characteristics, upon selecting electrolyte solutions for the individual sodium-ion battery system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,20] Interestingly, the negative impact of diglyme on conversion anodes comprising antimony oxide, as reported herein, was not observed with conversion anodes comprising tin compounds. [18,21] Hence, the unique interactions between Sn cations and diglyme molecules do not exist when we change the central transition metal involved in the electrode's conversion reactions. This situation emphasizes the importance of a proper adjustment of specific characteristics, upon selecting electrolyte solutions for the individual sodium-ion battery system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diglyme is considered as a promising alternative to alkyl carbonate-based electrolyte solutions in the state-of-the-art literature. [18][19][20] On the contrary to the results of Li et al [18] , Brehm et al [21] found that antimony shows very poor stability in the diglymebased electrolyte solutions when compared to other studies where alkyl carbonate-based electrolyte solutions were used. [16,22,23] The reason was not further evaluated, offering a basis for this work.…”
Section: Introductionmentioning
confidence: 91%
“…Very recently, ether-based electrolytes have been more widely investigated for graphite, [32] hard carbon, [33] Bi, [34,35] and Sn based electrodes [36,37] [17] due to their generally enhanced compatibility with many anode materials (Sb being an exception [36] ). Note that the stability of the electrolyte is also depending on the type of conductive salt used with sodium trifluoromethanesulfonate (NaOTf) and NaPF 6 being clearly favored (at least in half-cell experiments).…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, a class of promising high capacity materials like tin, phosphorus, or antimony which can form Na-rich compounds through an alloying reaction was proposed in the literature. 5,[10][11][12][13] A key issue of alloy-based materials is the severe capacity fading, which prevents the commercialization of such anodes. 10,14 The main reason for this fading is the large volume change during sodiation and desodiation, which can lead to aggregations and slower kinetics.…”
Section: Introductionmentioning
confidence: 99%